Optimizing Investments in Mozambique's Tuberculosis Response : Results of a Tuberculosis Allocative Efficiency Study - Mozambique National TB Program; World Bank; Optima Consortium for Decision Sciences; Burnet Institute (World Bank, Washington, DC, 2020)
This allocative efficiency analysis intended to assess Mozambique's progress towards TB strategic targets, and provide decision support for TB strategy using a combined TB epidemiological component and an economic and program analysis framework (Optima TB). Input data were collected from NTP sources, the WHO, and various TB implementers. Our model indicates declining future trends in TB prevalence, incidence and related deaths. However, the case detection rate (52 percent) remains one of the biggest hurdles. Mozambique, however, could cut TB prevalence and TB deaths by 20 percent, and TB incidence by 11 percent by allocating resources optimally. Specifically, this would entail (i) doubling the rate of household contact tracing for notified cases, (ii) screening all PLHIV during their routine outpatient visits, and (iii) focusing on community outreach activities among key populations such as prisoners, cross-border miners and community health workers. In addition, scaling up ART coverage from 55 percent (current/ 2017) to 90 percent by 2035 is projected to reduce new TB cases among PLHIV by over 50 percent (in 2035). Furthermore, our analysis shows that higher levels of TB spending lead to more rapid reductions in TB incidence. However, the rates of reduction associated with large increases in expenditure (up to 200 percent of current spending levels) begin to slow in the medium term and it is unlikely that the national TB response can deliver on the 2025 milestones and 2035 End-TB targets.